Cultivo in situ de folículos ovarianos pré-antrais de cabras com esfingosina (S1P) e fator inibidor da leucemia (LIF) - Nóbrega Junior, Jandui Escarião da (2011)
The manipulation of oocytes enclosed in follicles Ovarian Pre-Antral, allows increasing the reproductive potential of females from the isolation and cultivation. The follicular viability can be affected negatively correlated with age, malnutrition, exposure to radio or chemotherapy and health conditions. The alternatives are to use these research for development of culture media which provides the maintenance of viability allows the activation and follicular development in vitro, for subsequent fertilization. Physiologically various growth factors are involved in the process of folliculogenesis, many of which have so far not been tested in goats. Among them the Sphingosine 1-phosphate (S1P) and Leukemia Inhibitory Factor (LIF), since, follicular development were obtained with these factors in other species, allowing follicular growth and ant apoptotic effect on ovarian tissue. The aim of this study was to evaluate the addition of different concentrations of S1P and the LIF to culture media separately, evaluating the maintenance of viability, activation and follicular development. Thus, the preantral follicle cultured with S1P in situ LIF for 7 days and follicular development as possible to maintain viability, activation and growth of preantral follicle in vitro. Concluding that the S1P 1 ng/ml LIF and 10ng/ml, were the concentration that the maintenance of viability and follicular activation of in situ and grown in vitro for 7 days improved the viability, activation and preantral follicular growth.